Eating Behavior of Nursing Students at Tertiary Care Teaching Institute in Uttarakhand: A Cross-Sectional Analytical Study - Srishti Bhatt; Vaneet Kaur; Sukhman; Usha Devi; Sonika; Shweta Deswal; Simran; Shruti Joshi; Shweta Gautam; Shiv K Mudgal; Suresh K Sharma (Medsci Publications, 2020)
Introduction: Promoting healthy lifestyle is among young nurses is necessary to promote overall health. Present study aimed to assess the dietary pattern among nursing students and also to determine the association of dietary patterns with their demographic and eating habits variables. Methods: Present study was conducted among 112 nursing students who were selected through proportionate stratified random sampling technique from a tertiary care teaching institute in Uttarakhand. Data regarding students' dietary pattern was collected through a self-structured Likert scale on unhealthy dietary pattern and healthy supplementation pattern. Descriptive and inferential statistics were used for data analysis using SPSS. Results: Study results have shown that mean and standard deviation for unhealthy dietary pattern and healthy supplementation pattern were 24.58±7.61 and 34.85±8.64 respectively. Using ANOVA, significant association was observed for students' eating habits (meal regularity, main meal of the day and frequency of eating outside) with unhealthy dietary pattern and healthy supplementation pattern at p<0.05. Conclusion: Nursing students can serve as an important link to spread community awareness about the benefits of healthy eating which can promote health and well-being in community at large.